Synthesis and characterisation of layered double hydroxides with varying divalent metal cations: Mg2+, Zn2+, Ca2+ - Limau Jadam M.; Halimah Sarijo S.; Jubri Z. (Elsevier Ltd, 2023)
Aluminum compounds; Fourier transform infrared spectroscopy; Magnesium; Nitrates; Physicochemical properties; Positive ions; Precipitation (chemical); Scanning electron microscopy; Thermogravimetric analysis; Zinc; Ca 2+; Fourier transform infrared spectra; Hydrocalumite; Hydrotalcites; Layered-double hydroxides; Magnesium-aluminum layered double hydroxides; Synthesised; Zinc aluminiums; Zinc-aluminum; Zn 2+; Calcium